Pertanggungjawaban Rumah Sakit terhadap Dokter yang Melakukan Malpraktik - Reza Havrian (Wajah Hukum, 2020)
Hospital is a health care institution that organizes individual health services in a plenary that provides inpatient, outpatient, and emergency services. In Indonesia, the practice of hospitals is governed by the law No. 44 year 2009 about hospitals. The law, in addition to being a basic guideline for legal and administrative, is also made to provide legal certainty in the maintenance of health services, as well as provide protection for the Community and protection of resources People in hospitals. Currently, hospitals can be held accountable because the condition of the hospital is no longer an institution that only focuses on the principle to help people only. The hospital slowly changed its function into a profit-oriented corporation. This is because the growing of science and technology are valued so much that doctors and hospitals also need additional costs for survival. The provisions of the hospital are responsible for the loss of a person as a result of the action of health workers, this is a request for the hospital to be responsible for te actions taken by the officers of his subordinates either as the status Fixed or not fixed. Doctors as a party to the agreement by the hospital do have the achievement to seek the healing of the patient through the search for the most appropriate therapy and not on promising healing from the patient. Therefore, doctors have a responsibility for the actions that do not only take the best effort according to the knowledge and experience he possesses. The hospital's accountability to doctors who do malpractice is not absolute and has many gaps. Unlike the damages to civil law, criminal liability can still be made by using the doctrine of corporate accountability.